Biodiesel fuels - Knothe, Gerhard (Animo Repository, 2017)
The mono-alkyl esters, most commonly the methyl esters, of vegetable oils, animal fats or other materials consisting mainly of triacylglycerols, often referred to as biodiesel, are an alternative to conventional petrodiesel for use in compression-ignition engines. The fatty acid esters that thus comprise biodiesel largely determine many important fuel properties. In turn, the composition of the biodiesel depends on the composition of the parent feedstock because feedstocks with widely varying fatty acid composition can be used for biodiesel production. The use of different feedstocks is also significant under aspects of increasing biodiesel supply and socio-economic issues. In this article, biodiesel production is briefly described, followed by a discussion of biodiesel fuel properties and the influence of varying fatty acid profiles and feedstocks. It is shown that the properties of biodiesel least influenced by minor components can be determined by a straightforward equation in which the properties of the biodiesel fuel are calculated from the amounts of the individual component fatty esters and their properties. Optimizing biodiesel composition is also addressed. © 2016